Relevansi pendidikan kejuruan terhadap pasar kerja di Kota Salatiga - Ngadi (Jurnal Kependudukan Indonesia, 2014)
Thispaper aimed to discuss the relevance of vocational education on labor market mainly on labor absorption and productivity. Data for analysis are research data 2011 in Salatiga that were collected by secondary data, interview, and observation. Analysis showed that vocational educations have high contribution on labor market. However, the relevance of vocational education to labor market has not been encouraging because about 12 percent of vocational education graduates are not absorbed in the labor market. In other sides, the average income of vocational educations graduates are lower than tertiary school graduates so the productivity of vocational education is still not satisfactory. Those were indicate that rate of return of vocational education lower than tertiary education. Thus, vocational educations need to be developed both in input and learning process so they can create more competitiveness graduation. Positively, some of the vocational educations have been able to make link and cooperation with business and industry. Eventhough, some of them have been able to get a good job before passed from school.